From rhetoric to reality: an NGO's challenge for reaching the furthest behind. Issue 7 (3rd October 2017) - Stanley, Andrew C.; Willms, Dennis; Schuster-Wallace, Corinne; Watt, Susan
ABSTRACT: The guiding principle of Agenda 2030 is the commitment to "leave no one behind". However, as the Millennium Development Goals experience has demonstrated, there remains a "rhetoric-implementation gap" where local stakeholders struggle to realistically respond to policies formulated at the global level. This article proposes a way forward for NGOs seeking to translate the rhetoric of Agenda 2030 into reality. It presents an integrated and multi-sectoral approach to meet the challenges of an NGO working to ameliorate the basic needs of women who are affected by HIV/AIDS and limited WaSH provisions in the impoverished rural community of Lyantonde, Uganda.